Dynamics of Genotypic and Phenotypic Antibiotic Resistance in a Conventional Wastewater Treatment Plant in 2 Years - Shin, Hanseob; Kim, Yeonghyeon; Raza, Shahbaz; Unno, Tatsuya; Ryu, Song-Hee; Hur, Hor-Gil (Frontiers in Microbiology, 2022)
Wastewater treatment plants (WWTPs) are considered a sink and a source of antibiotic resistance. In this study, we applied both culture-dependent and SmartChip-based culture-independent approaches for the investigation of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) at Jungnang (JN), located in the Han River, Seoul, South Korea, for 2 years, i.e., 2017 and 2018. The JN WWTP reduced the diversity and abundance of ARB and ARGs but was not sufficient for removing them all. Interestingly, through the treatment process in the JN WWTP, the composition of diverse multidrug-resistant (MDR) bacteria was concentrated mainly into some genera of the Gammaproteobacteria class (Citrobacter, Escherichia-Shigella, and Stenotrophomonas), which could be key carriages to spread ARGs into the environments. In addition, SmartChip analyses showed that the relative abundance and the number of ARGs were significantly decreased from the influents to the effluents in both 2017 and 2018. SmartChip analyses for 2 years also allowed to notify the core ARGs in the influents and the effluents with the presence of clinically relevant core ARGs, such as vanC, blaOXA, and blaNDM, which persisted in the treatment process. Considering diverse bacterial mechanisms for exchanging and transferring ARGs, the occurrence of MDR bacteria and core ARGs could be a source for the blooming of the antibiotic resistome in the WWTP and nearby environments.